2021
DOI: 10.3389/fnut.2021.706552
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Agriculture Development in Northwest China Under the Impacts of Global Climate Change

Abstract: Northwest China has one of the most vulnerable agricultural systems in the context of global climate change. We argue that sustainable agriculture development in this region requires a systematic approach toward climate change adaptation, and propose a schematic framework for strategic thinking. We first briefly review the impacts of climate change on various agricultural environmental factors, including light, temperature, water, and atmosphere, and explores the effects of climate change on agricultural pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In addition, the ecological habits of C. henryi with a marked preference for warm and humid conditions could take advantage of the increasing favorable setting brought by climate change. Warmth‐preferring species, including C. henryi , would therefore continue to benefit from moderate climate change (Liu, Li, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ecological habits of C. henryi with a marked preference for warm and humid conditions could take advantage of the increasing favorable setting brought by climate change. Warmth‐preferring species, including C. henryi , would therefore continue to benefit from moderate climate change (Liu, Li, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable food production and food security are major issues of the 21st century under a changing climate because the agriculture sector is most vulnerable to climate change [1,2]. Climate change is already affecting agricultural production and food security and will continue to affect it in the future, especially in developing countries [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, the rapid rise in the prices of agricultural products is becoming an important reason for the weakening of their global competitiveness in the agricultural sector [34,53]. Numerous researchers suggested that it is critical to resolve the high cost of agricultural production by adopting affordable agricultural technology, which helps mitigate climate change and protect the environment [1,54]. Further, modern technology helps growers decrease production costs significantly, improve farming production efficacy, and decrease labour force inputs effectively [55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Target 6 also addresses that by 2030, substantially increase water-use efficiency across all sectors and ensure sustainable withdrawals and supply of fresh water to reduce the number of people suffering from water scarcity (GEMI 2019). According to the Intergovernmental Panel on Climate Change (IPCC), maize, wheat, and other major crops have experienced significant yield reductions at the global level of 40 megatons per year between 1981 and 2002 due to a warmer climate (Liu et al 2021a(Liu et al , 2021b. SDG 11 indicates that by 2030, substantially decrease the direct economic losses relative to global gross domestic product caused by disasters (Lee et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In response to the water crisis, governments around the world have been vigorously studying agricultural watersaving policies, measures and technologies in recent decades. Liu et al (2021aLiu et al ( , 2021b introduced the 'Water-Saving Management Contract' used in China, which was an innovative business model aimed at reducing water consumption and improving water use efficiency. Mourad et al (2011) evaluated the potential for potable water saving by greywater reuse in Syrian.…”
Section: Introductionmentioning
confidence: 99%